85 Enhanced nuclear RSK1 signalling promotes cardiac hypertrophy in mice in vivo, but compromises compensated hypertrophy induced by phenylephrine. (June 2018) - Clerk, Angela; Rostron, Kerry; Meijles, Daniel; Fuller, Stephen; Sugden, Peter
Abstract : Background: The α1-adrenergic receptor (α1AR) agonist phenylephrine (PE), acts via ERK1/2 to phosphorylate (i.e. activate) p90 ribosomal S6 kinases (RSKs). PE promotes compensated hypertrophy and increases cardiomyocyte size. ERK1/2 and RSKs phosphorylate transcription factors producing changes in gene expression. In cardiomyocytes, potent ERK1/2 signalling causes nuclear-localisation of activated RSK1/RSK2 isoforms. This promotes cardiomyocyte growth, but hypertrophy is not sustained. Lesser ERK1/2 activation by PE causes nuclear activation of only RSK2, and this signalling is associated with a different gene expression profile. Our hypothesis is that activation of nuclear-localised RSK1 in addition to RSK2 promotes changes in gene expression that are not compatible with compensated hypertrophy induced by α1ARs. Our aim was to investigate if expression of nuclear-localised RSK1 is detrimental to the hypertrophic response induced in vivo by PE. Methods/results: Nuclear-localised (NL) RSK1 or RSK2 were expressed in cultured cells using adenoviral vectors. Immunostaining confirmed expression of NL-RSKs was confined to nuclei of HEK293, SVEC (endothelial cells) or neonatal rat cardiomyocytes. By immunoblotting with antibodies for phosphorylated (i.e. activated) RSKs, we confirmed that NL-RSKs were inactive in serum-starved cells, and activated following treatment with epidermal growth factor. We generated transgenic mice for tamoxifen-inducible, cardiomyocyte-specific expression of NL-RSK1 by inserting the transgene in the ROSA26 locus, separated from the promoter by a LoxP-flanked stop cassette. NL-RSK1 mice were crossed with mice with tamoxifen (Tam) inducible CRE under control of the α myosin heavy chain promoter, producing double heterozygotes and wild-type (WT) littermates for experiments (n=9 per group). Echocardiography was used to assess cardiac function/dimensions at baseline and following treatment. There was no significant difference between transgenic mice and WT litter mates up to 10 weeks of age in any of the variables studied. Tam-treatment (7 d) significantly increased diastolic (d) or systolic (s) left ventricular (LV) posterior wall (PW) thickness (16%) in transgenic, not wild-type (WT) mice indicating that enhanced NL-RSK1 alone promotes hypertrophy. PE (40 mg/kg/d, 3 d) increased LVPW~99% in WT or transgenic mice with corresponding decreases in LV internal diameters, but the degree of hypertrophy was significantly reduced (~45%) in transgenic mice pretreated (4 d) with Tam. Conclusions: Increased nuclear-localised RSK1 in cardiomyocytes promotes cardiac hypertrophy, but compromises the compensated hypertrophic response to PE. Selective inhibition of RSK1 (rather than RSK2) may preserve the compensated hypertrophic state and, thus, reduce heart failure progression.